The impact of online identity theft on customers' willingness to engage in e-banking transaction in Ghana: A technology threat avoidance theory - Abdul Bashiru Jibril; Michael Adu Kwarteng; Raphael Kwaku Botchway; Jürgen Bode; Miloslava Chovancová (Cogent Business & Management, 2020)
Until recently, studies regarding e-banking transactions have focused more on motivational factors that trigger the intention to accept and use the e-banking transaction, rather than the de-motivational factors that propel the action. However, in the developing countries like Sub-Sahara economies, the factors associated with the former have not been explored and are still rudimentary in the literature. Drawing from the Technology Threat Avoidance Theory (TTAT), the study seeks to examine the impact of online identity theft on customers' willingness to engage in e-banking transactions in Ghana. A quantitative survey of 393 valid responses from retail bank customers amongst two leading commercial banks in Ghana for the analyses. Results from the PLS-SEM showed that the research constructs; perceived online identity theft' positively and significantly predict "fear of financial loss", "fear of reputational damage", and "security and privacy concern" whilst the former has a negative mediated-relationship between perceived online identity theft and the intention to engage in e-banking transaction. This study is the first of its kind that has extended the application of the TTAT framework into the study of e-banking transactions. The study serves as a practical tool that will enable the banks in their quest to assess customers' restriction/aversion towards the use of Fintech while ensuring sustainable growth of e-banking transactions in an emerging economy context. The study is limited to only banking institutions in Ghana without considering other players in the financial sub-sector. Future research direction has been suggested in the concluding part of the paper.
Keywords: 650; Online identity theft; e-banking transaction; technology threat avoidance theory; bank customers; Sub-Saharan Africa; developing country; Ghana